Optimalisasi Pemasaran Digital Produk Olahan Daun Kelor Berbasis Marketing 5.0 untuk Mendorong UMKM 'Dapur Aru' Naik Kelas di Kabupaten Kampar - Desmawati Desmawati (Unri Conference Series: Community Engagement, 2025)
This study aims to analyze and optimize the digital marketing strategy of processed moringa leaf products implemented by ‘Dapur Aru’ MSMEs in Kampar Regency to encourage them to move up a class. The study used a descriptive qualitative approach with a case study method. Data were collected through in-depth interviews, observations and documentation with MSME owners, business assistants and relevant government agencies. The results show that ‘Dapur Aru’ MSMEs have utilized social media such as WhatsApp and Facebook, but their use is still limited to simple promotions and is inconsistent. The main obstacles include limited digital literacy, minimal training, and low utilization of marketplaces. The proposed optimization strategy includes increasing digital capacity through training, content marketing assistance, and collaboration with external parties such as universities and local communities. This research provides a practical contribution to strengthening the competitiveness of herbal product MSMEs in the digital era and provides empirical evidence of the application of the Marketing 5.0 approach to locally-based MSMEs.